Chemoradiotherapy versus chemotherapy as adjuvant treatment for localized gastric cancer: a propensity score-matched analysis - Girardi, Daniel M. (BMC Cancer, 2018)
BACKGROUND: Treatment of localized gastric cancer (LGC) consists of surgical resection followed by adjuvant treatment. Both chemoradiation (CRT) and chemotherapy (CT) regimens have shown benefit in survival outcomes versus observation. However, there are few data comparing these approaches. METHODS: This study included consecutive patients with LGC treated at Instituto do Cancer do Estado de Sao Paulo (ICESP) from 2012 to 2015. CRT was based on the INT-0116 regimen and CT consisted of a platinum and fluoropyrimidine doublet. Treatment choice was based on physician preference. Toxicity was evaluated for every cycle. Overall survival (OS) analysis was performed by Kaplan-Meier. A propensity score-matched analysis was performed to minimize selection bias. RESULTS: A total of 309 patients were evaluated, 227 in CRT group and 82 in CT group. The most prevalent grade 3/4 toxicities in CRT and CT groups were: nausea/vomiting (9.25 vs 4.9%), fatigue (9.3% vs 2.4%), mucositis (4.4% vs 1.2%), neutropenia (37.8% vs 20.9%), febrile neutropenia (3.9% vs 0%), anemia (4.3% vs 6.1%), thrombocytopenia (2.6% vs 4.9%), neuropathy (0 vs 2.4%) and hand-foot syndrome (0.4% vs 2.4%). Two grade 5 toxicities (febrile neutropenia and anemia) occurred in CRT group. There was no difference in the pattern of recurrence. After a median follow-up of 23.5 months (CRT) and 20.6 months (CT), there was no difference in OS between groups. CONCLUSIONS: CT and CRT present similar efficacy and tolerability as adjuvant treatment for LGC.